Maternal effects shape offspring physiological condition but do not senesce in a wild mammal. (3rd March 2021) - Cheynel, Louise; Gilot‐Fromont, Emmanuelle; Rey, Benjamin; Quéméré, Erwan; Débias, François; Duhayer, Jeanne; Pardonnet, Sylvia; Pellerin, Maryline; Gaillard, Jean‐Michel; Lemaître, Jean‐François
Abstract: In vertebrates, offspring survival often decreases with increasing maternal age. While many studies have reported a decline in fitness‐related traits of offspring with increasing maternal age, the study of senescence in maternal effect through age‐specific changes in offspring physiological condition is still at its infancy. We assessed the influence of maternal age and body mass on offspring physiological condition in two populations of roe deer ( Capreolus capreolus ) subjected to markedly different environmental conditions. We measured seven markers to index body condition and characterize the immune profile in 86 fawns which became recently independent of their known‐aged mothers. We did not find striking effects of maternal age on offspring physiological condition measured at 8 months of age. This absence of evidence for senescence in maternal effects is likely due to the strong viability selection observed in the very first months of life in this species. Offspring physiological condition was, on the other hand, positively influenced by maternal body mass. Between‐population differences in environmental conditions experienced by fawns also influenced their average body condition and immune phenotype. Fawns facing food limitation displayed lower values in some markers of body condition (body mass and haemoglobin levels) than those living in good quality habitat. They also allocated preferentially to humoral immunity, contrary to those living in good conditions, which allocated more to cellular response. These results shed a new light on the eco‐physiological pathways mediating the relationship between mother's mass and offspring condition. Abstract : In roe deer, maternal age does not have a negative impact on offspring physiological condition measured at 8 months of age. Offspring physiological condition is, however, positively influenced by maternal body mass. Between‐population differences in environmental conditions experienced by fawns also influence their average body condition and immune phenotype.